Analisis Efektivitas Sistem Informasi Akuntansi Terhadap Proses Pelayanan Nasabah pada Bagian Customer Service di PT Bank Sumsel Babel Syariah Capem Muhammadiyah Palembang - Emilia Gustini; Yulia Pita Sari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the effectiveness of the implementation of the Accounting Information System (AIS) in supporting customer service processes in the Customer Service department at PT Bank Sumsel Babel Syariah Capem Muhammadiyah Palembang, as well as to identify technical obstacles and their handling efforts. The research method used is descriptive qualitative with a case study approach through direct observation during the internship period. The results show that the implementation of the AS/400 platform-based AIS has been carried out systematically and structurally, becoming the operational backbone that supports speed and accuracy in customer service, as well as reflecting the application of Sharia accountability principles (shidiq, amanah, fathanah). However, the effectiveness of the system still faces operational obstacles, namely network fluctuations, a text-based interface that is less intuitive for new staff, and queue buildup during peak seasons. Handling efforts include temporary manual procedures, mentoring programs by senior staff, and queue flow optimization. Overall, the AIS has contributed positively to service efficiency, although improvements in network infrastructure stability and human resource competency development are needed to optimize system performance in the future.